The Perspective of Islamic Educational Philosophy in the Implementation of a Love Based Curriculum at the Provincial Education Office of South Sumatra - Triasih, Asti; Zainuri , Ahmad; Annur, Saiful (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The perspective of Islamic educational philosophy on the implementation of a love-based curriculum within the Education Office of South Sumatra Province. Islamic educational philosophy is rooted in the values of the Qur'an and Hadith, which emphasise a balance between the development of intellect, spirituality, and the cultivation of noble character. In this context, a love based curriculum is understood as an educational approach that places affection, respect for human dignity, and harmonious relationships between educators and learners at the core of the learning process. Through literature review and descriptive qualitative analysis, this article examines the relevance of the concept of love in Islamic education to regional educational policies, particularly in South Sumatra. The findings of the study indicate that the implementation of a love based curriculum aligns with the principle of rahmah in Islam, which encourages the emergence of learners who are not only intellectually outstanding but also empathetic, ethical, and possess a high social awareness. The application of this curriculum can create a learning atmosphere that is humanistic, participatory, and oriented towards character formation. Furthermore, the implementation of a love based curriculum is believed to serve as a strategic instrument in strengthening Islamic values, enhancing the quality of human resources, and providing education that is relevant to the modern challenges of the global era.